The Implementation Of English Questioning In Teaching Biology To The Third Grade Students Of RSBI Class At SMP Negeri 3 Sujoharjo - Pratistyantoro, Fendhi (2012)
In this research, the writer describes the process of The Pioneer of International Standard School (RSBI) at SMP Negeri 3 Sukoharjo. It indicates that this school has had the experience of the process of learning using two languages. It is conducted to describe the process of the teacher asking question, the type of questions addressed to the students, the students response the question. This research uses qualitative research. The subject of the study is the teacher of RSBI class and the third year students at SMP Negeri 3 Sukoharjo. The object of the research is the bilingual program and the implementation of English questioning. The data is collected from interviews and the data sources are event, informant and document. The techniques of collecting data are observation, interview, and documentation. The most significant difficulty in the implementation of English questioning in teaching Biology to the third grade students of RSBI class at SMP Negeri 3 Sukoharjo is the language. The teacher uses some techniques in asking question in Biology of RSBI class, they are table and group discussion. The teacher uses some questions in teaching learning Biology of RSBI class. They are W5H, open question, close question, funnel question, probing question, leading question, demonstration, prompting question, and redirecting. In teaching Biology to the third grade students of RSBI class, the students are passive in teaching learning process.